O projeto político-pedagógico como parâmetro na avaliação dos cursos de graduação: a experiência do conhecer, avaliar, melhorar - Figueira Neto, Arlindo Ornelas (Revista de Graduação USP, 2017)
We recognize the importance of student evaluation on our undergraduate courses, but, at same time we face the difficulty of measuring the effectiveness of the formation by the opinions of those who don’t have a complete and a prospective view of their education needs. This dissonance was the starting point of the Conhecer, Avaliar, Melhorar project, that was focused on undergraduate student evaluation, based on the dissemination and discussion of the PPP (Political Pedagogic Project) of the course of Propaganda and Advertising of ECA (School of Arts and Communication). In a first step, the PPP itself was evaluated as its suitability to contemporary demands of employability; and, in a second level, it was questioned if and how the PPP was applied on disciplines and in the classrooms. Despite the various difficulties faced both by free choice variables, such as uncontrollable factors, it was possible to conclude that the idea is perfectly valid and appropriate for promoting student assessment of their courses in a more objective and conscious level.